Counseling for Street Children/Minors, Adolescents, and the Elderly with Lecturers from UINSI Samarinda: Bimbingan Anak Jalanan/Dibawah Umur, Remaja dan Lansia Bersama Dosen UINSI Samarinda - Abdul Majid; Iskandar; Imanuddin; M. Salim Said; Rosnaeni; Yeni Rahmawati (Wadah Inovasi Indonesia, 2023)
This research examines efforts in child protection and empowerment of vulnerable groups such as street children, underage children, adolescents, and the elderly in Samarinda City. The method of community service involves identifying needs through surveys and interviews, designing guidance programs based on best practices, conducting guidance sessions, and periodic evaluation. The results show that collaboration between educational institutions and local communities can have a positive and sustainable impact. Challenges include consistency in participation and logistical constraints, but development opportunities such as expanding partnerships and utilizing information technology are also identified. This research emphasizes the importance of child protection efforts and empowerment of vulnerable groups in achieving positive social change in the community